2006
DOI: 10.1007/510637-005-4827-3
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of chloroquinoxaline sulfonamide (CQS) in patients with metastatic colorectal carcinoma (MCRC)

Abstract: CQS, when given at a dose of 2000 mg/m2 weekly for 4 weeks every 42 days to patients with metastatic colorectal cancer, does not result in significant tumor regression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…The drugs were used either as single agents (66%) or in combination with existing chemotherapies (34%). While most trials completed as planned, three trials of indisulam and one trial of CQS terminated prematurely due to a lack of efficacy (Bekaii‐Saab et al, 2006; Eisai Inc., 2014a, 2014b; Haddad et al, 2004). Meanwhile, tasisulam treatment was associated with unexpected patient deaths, which led to early termination of three trials including one phase III trial with advanced melanoma patients (Eli Lilly and Company, 2018b, 2019b; Hamid et al, 2014).…”
Section: Targeting Rbm39 In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…The drugs were used either as single agents (66%) or in combination with existing chemotherapies (34%). While most trials completed as planned, three trials of indisulam and one trial of CQS terminated prematurely due to a lack of efficacy (Bekaii‐Saab et al, 2006; Eisai Inc., 2014a, 2014b; Haddad et al, 2004). Meanwhile, tasisulam treatment was associated with unexpected patient deaths, which led to early termination of three trials including one phase III trial with advanced melanoma patients (Eli Lilly and Company, 2018b, 2019b; Hamid et al, 2014).…”
Section: Targeting Rbm39 In Cancermentioning
confidence: 99%
“…Otherwise, these drugs were well tolerated in patients, and the most common dose‐limiting toxicities (DLTs) were neutropenia and thrombocytopenia (Table S1). Study results from 34 trials are available to this date (Assi et al, 2018; Bekaii‐Saab et al, 2006; Conley et al, 1995; Dittrich et al, 2003; Dittrich et al, 2007; Eli Lilly and Company, 2018a, 2018b, 2018c, 2018d, 2018e, 2018f, 2019a, 2019b; Fujiwara et al, 2013; Gordon et al, 2013; Haddad et al, 2004; Hamid et al, 2014; Jotte et al, 2015; Kirkwood et al, 2011; Miller et al, 1997; Milojkovic Kerklaan et al, 2016; Mita et al, 2011; Punt et al, 2001; Raymond et al, 2002; Rigas et al, 1992; Rigas et al, 1995; Ryan et al, 2013; Scagliotti et al, 2012; Siegel‐Lakhai et al, 2008; Simon et al, 2011; Smyth et al, 2005; Talbot et al, 2007; Terret et al, 2003; Yamada et al, 2005). No complete responses were observed, but a small number of patients had partial tumour regression (partial response) in four trials of indisulam, two trials of CQS and 11 trials of tasisulam (Tables 1 and S1).…”
Section: Targeting Rbm39 In Cancermentioning
confidence: 99%
“…Currently, there are two major types of medications that specially aim at the interactions between substrates and recognition receptors in order to exert anti-cancer impacts, namely sulfonamides and thalidomide derivatives, each characterized by specific mechanisms. Three members of anticancer sulfonamides E7820, CQS (chloroquinoxaline sulfonamide) and indisulam have displayed efficacy against various cancers, including colorectal cancer and melanoma [244][245][246] . However, their mechanisms of action remain poorly defined.…”
Section: Perspective and Therapeutic Implicationsmentioning
confidence: 99%
“…XK469 (NSC 697887) and CQS (NSC 339004), two synthetic quinoxaline derivatives without two oxygens on the quinoxaline ring, also show solid tumor selectivity. XK469 and CQS have entered Phase I and Phase II clinical study, respectively ( Miller et al, 1997 ; Bekaii-Saab et al, 2006 ; Alousi et al, 2007 ). Gao et al (1999) reported the primary target of XK469 is Topo IIβ, and CQS was found to be both a Topo-IIα and a Topo-IIβ poison ( Gao et al, 2000 ).…”
Section: Antitumor Activity Of Qdnosmentioning
confidence: 99%